2012
DOI: 10.1590/s0100-83582012000300018
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidas inibidores da ALS aplicados em pós-emergência no arroz de terras altas

Abstract: RESUMO -Este trabalho teve por objetivo avaliar a seletividade de herbicidas inibidores da ALS recomendados para arroz irrigado, quando aplicados em diferentes estádios de desenvolvimento do arroz de terras altas. O experimento foi conduzido em campo, no município de Nova Xavantina-MT, no período de novembro de 2009 a abril de 2010. O delineamento experimental foi o de blocos ao acaso, em esquema fatorial 5 x 3, composto pelos tratamentos herbicidas penoxsulam (36 g ha -1 ), bispyribac-Na (50 g ha), pirazosulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
2
0
3
Order By: Relevance
“…As for BRS Monarca, a reduction in number of panicles per m -2 was observed only with the application at 45 DAE, regardless of herbicide used. These results corroborate those obtained by Petter et al (2012), who have also found a reduction in the number of panicles per m -2 with the application of these herbicides at 45 DAE in upland rice.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As for BRS Monarca, a reduction in number of panicles per m -2 was observed only with the application at 45 DAE, regardless of herbicide used. These results corroborate those obtained by Petter et al (2012), who have also found a reduction in the number of panicles per m -2 with the application of these herbicides at 45 DAE in upland rice.…”
Section: Resultssupporting
confidence: 92%
“…However, as for the assessments at 14 and 28 DAA a significant difference for this variable was no longer detected, showing good resilience of these cultivars to the deleterious effect of these herbicides. Similar behavior was observed by Petter et al (2012) in plants of upland rice cv. BRS Sertaneja, in which plants recovered from the deleterious effects in their height due to the application of herbicides bispyribac-sodium, penoxsulan and pyrazosulfuron-ethyl.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Os sintomas visuais de fitotoxicidade e o prejuízo ao sistema de raízes e parte aérea das plantas algumas semanas após a aplicação foram verificados para ambos os herbicidas, por vezes afetando, outras não, alguns componentes ou a própria produtividade, mas quase sempre com forte dependência dos outros fatores relacionados, seja das doses utilizadas, épocas de aplicação, cultivares ou manejos adotados (BOND et al, 2007;CONCENÇO et al, 2007;PETTER et al, 2012;ZUFFO;PACHECO, 2011;WILLINGHAM et al, 2008). A produtividade da cultura do arroz pode ser afetada em diversos momentos, isto é, nos estádios de desenvolvimento em que cada um dos seus componentes está sendo definido; um estresse pode comprometê-lo, podendo reduzir o volume final de sementes colhido.…”
Section: Resultsunclassified